Comparison of Corn, Grain Sorghum, Soybean, and Sunflower under Limited Irrigation. (1st March 2016) - Schlegel, Alan J.; Assefa, Yared; O'Brien, Dan; Lamm, Freddie R.; Haag, Lucas A.; Stone, Loyd R.
Abstract : Corn ( Zea mays L.) and soybean [ Glycine max (L.) Merr.] constitute a large share of the annual total irrigated planted area in the central Great Plains. This study aimed to determine the effect of limited irrigation on grain yield, water use, and profitability of corn and soybean in comparison with two crops commonly grown in water‐limited environments (grain sorghum [ Sorghum bicolor (L.) Moench.] and sunflower [ Helianthus annuus L.]). The study was conducted at Tribune, KS, from 2001 to 2008, with a mean April to October rainfall of 390 mm. Treatments were a complete factorial of four crops and three irrigation levels: 127, 254, and 381 mm. At all irrigation levels, the mean grain yield of corn was greater than that of grain sorghum, followed by soybean and sunflower. The grain yield of sorghum, soybean, and sunflower was 19%, 16%, and 33%, greater, respectively, at 254 mm than at 127 mm irrigation, but similar for the 254 and 381 mm irrigation levels. Corn grain yield was 49% greater with 254 mm than with 127 mm irrigation and increased by an additional 17% under 381 mm irrigation. Available soil water in the 0‐ to 30‐cm soil depth at harvest was ∼19 mm for corn and ∼31 mm for sorghum. Under limited irrigation conditions (127 mm), we have concluded that producers have multiple crop choices (corn, sorghum, soybean, or sunflower) with small yield and economic differences and, at higher irrigation levels (254 and 381 mm), a relative yield and economic advantage for corn.